Reliability of HOME FAST BRAZIL—Self-Reported Version for Community-Dwelling Older Adults - Ferreira, Karina Stella Aoki; Gallo da Silva, Tamires Terezinha; Melo Filho, Jarbas; Bazanella, Natacha Verônica; Vojciechowski, Audrin Said; Mackenzie, Lynette; Gomes, Anna Raquel Silveira (Frontiers in Public Health, 2021)
Objective: Verify the intra- and inter-rater reliability of the HOME FAST BRAZIL—Self-reported version and correlate household environmental risks with the history of falls by community-dwelling older adults. Method: Cross sectional study with 50 community-dwelling older adults who were screened by the cut-off point of the Mini Mental State Exam and replied to the HOME FAST BRAZIL—Self-reported version using two evaluators, on three occasions. The reliability analysis was determined by the Intra-class Correlation Coefficient (ICC), considering ICC > 0.70 as adequate. To test the correlations, the Spearman test was used. Results: The mean age of the participants was 73.2 ± 5.8 years. The inter- rater reliability of HOME FAST BRAZIL—Self-reported version was ICC 0.83 (IC95%, 0.70–0.90) and the Intra- reliability ICC 0.85 (IC95%, 0.74–0.91). A risk of falls was verified in 88% of the sample and four environmental risks presented significant correlations with the history of falls. Conclusions: The HOME FAST BRAZIL—Self-reported version presented adequate reliability for the evaluation of household environmental risks for community-dwelling older adults. Risks such as inadequate armchairs/ sofas, the absence of anti-slip mats in the shower recess, the presence of pets and inadequate beds require attention in the evaluation of household risks, due to their correlation with the occurrence of falls.